Fossil‐based comparative analyses reveal ancient marine ancestry erased by extinction in ray‐finned fishes. (23rd March 2015) - Betancur‐R, Ricardo; Ortí, Guillermo; Pyron, Robert Alexander; Morlon, Helene
Abstract The marine‐freshwater boundary is a major biodiversity gradient and few groups have colonised both systems successfully. Fishes have transitioned between habitats repeatedly, diversifying in rivers, lakes and oceans over evolutionary time. However, their history of habitat colonisation and diversification is unclear based on available fossil and phylogenetic data. We estimate ancestral habitats and diversification and transition rates using a large‐scale phylogeny of extant fish taxa and one containing a massive number of extinct species. Extant‐only phylogenetic analyses indicate freshwater ancestry, but inclusion of fossils reveal strong evidence of marine ancestry in lineages now restricted to freshwaters. Diversification and colonisation dynamics vary asymmetrically between habitats, as marine lineages colonise and flourish in rivers more frequently than the reverse. Our study highlights the importance of including fossils in comparative analyses, showing that freshwaters have played a role as refuges for ancient fish lineages, a signal erased by extinction in extant‐only phylogenies.